2022
DOI: 10.1021/acs.estlett.2c00431
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the Tire Rubber-Derived Contaminant 6PPD-Quinone Causes Mitochondrial Dysfunction In Vitro

Abstract: N-(1,3-Dimethylbutyl)-N′-phenyl-p-phenylenediaminequinone (6PPD-quinone), a rubber tire oxidation product found in road runoff, is highly and acutely toxic to selected salmonids including coho salmon, brook trout, and rainbow trout but not other fish species and invertebrates studied to date. Sensitive species displayed increased ventilation and gasping, suggesting a possible impact on respiration. Here, adherent cell lines RTL-W1 and RTgill-W1 were exposed to 5− 80 μg/L 6PPD-quinone, and cytotoxicity, oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 32 publications
(59 reference statements)
5
45
3
Order By: Relevance
“…The suspected monohydroxylated metabolite was detected in all exposure samples (Figure ), indicating the ability to metabolize 6PPD-Q by brain and gill in three tested species. This observation is inconsistent with the previous study demonstrating no detectable monohydroxylated metabolite in rainbow trout gill cells (RTgill-W1) exposed to 6PPD-Q . The reasons for the inconsistency are unknown but might be related to the difference between in vivo and in vitro systems .…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The suspected monohydroxylated metabolite was detected in all exposure samples (Figure ), indicating the ability to metabolize 6PPD-Q by brain and gill in three tested species. This observation is inconsistent with the previous study demonstrating no detectable monohydroxylated metabolite in rainbow trout gill cells (RTgill-W1) exposed to 6PPD-Q . The reasons for the inconsistency are unknown but might be related to the difference between in vivo and in vitro systems .…”
Section: Resultscontrasting
confidence: 99%
“…The recovery ratios of 6PPD-Q during the extraction were estimated to be 96 ± 14% (brain) and 102 ± 11% (gill) using wet tissue taken from a clean culture spiked with 0.1 μg of 6PPD-Q per sample ( n = 3; mean ± standard deviation). Also, the suspected monohydroxylated metabolite of 6PPD-Q was semiquantified on the basis of the transition from m / z 315 to 231 according to a recent study for selected samples (i.e., the highest and second highest concentrations for S. leucomaenis pluvius and all concentrations for the other two). The semiquantification assumed the response was equal to that of 6PPD-Q due to the unavailability of the analytical standards.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that a portion of 6PPD and 6PPD-Q may also be excreted through feces and exhaled air like some other pollutants, , the actual exposure dose of 6PPD and 6PPD-Q may even be higher than our estimates. Although the dose is unlikely to exceed a proposed reference dose (RfD) of 26000 (ng/kg bw)/day calculated for 6PPD, the potential health risk posed by long-term exposure to 6PPD-Q requires considerable attention, as 6PPD-Q has been proven to be more toxic to aquatic organisms than 6PPD from the individual species to the tissue levels. ,, In future studies, additional biomonitoring investigations on 6PPD and 6PPD-Q are needed to better elucidate their internal exposure in humans. More toxicological and epidemiological studies of 6PPD and 6PPD-Q are also recommended to shed light on their potential health risks.…”
Section: Resultsmentioning
confidence: 99%
“…Mahoney et al also found that 6PPD-quinone might disrupt mitochondrial respiration of rainbow trout gill cells (RTgill-W1). The oxygen consumption rate was increased rapidly in 15 min in RTgill-W1 cell after being exposed to 5–80 μg/L 6PPD-quinone, implying the tissue-specific toxicity of 6PPD-quinone [ 55 ]. 6PPD-quinone was also observed to be highly toxic to silver salmon with an LC 50 of 0.79 ± 0.16 μg/L, which is almost three orders of magnitude lower than that of 6PPD [ 7 ].…”
Section: Toxic Effects Of Antioxidants and Tpsmentioning
confidence: 99%